Prevalence of ß-Thalassaemia in African Descendent Lyari Population - Durr-e-Sameen, Akbar Agha, Shaheen Agha, Sulaiman Ahmad, Nadeem Nusrat, Saima Minhas, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To assess the prevalence of beta thalessemia Trait in the African descendant Population, of Layari Karachi Pakistan. Study Design: Descriptive cross-section study Place & Duration: Samples collected at Lyari General Hospital, Karachi & Tested at Dow Institute of Haematology . DUHS. Karachi, from October 2012 March 2013. Material & Methods: We studied 200 consecutive subjects of Makrani cast of both genders, who visited Lyari General Hospital during the study period. The demographic data was entered on a proforma. CBC, peripheral smear and haemoglobin electrophoresis was performed on all samples. Result:The male to female ratio of the study population was found to be 0.59:1. 5 patients of ß- thalassaemia major and 27 patients of ß- thalassaemia trait were detected on electrophoresis with over- all frequency of 16% , 2.5% for major and 13.5% for trait in our study population. The overall percentage of family marriages in the study group was 59%. In thalassaemic trait group it was 77%, while in diseased group 100% of the patients gave history of parental consanguinity. Conclusion: The prevalence of ß-thalassaemia in Makrani cast of Lyari is found to be quite high i.e. 16%,common custom of family inter marriages was also detected which may be one of the cause of high frequency of haemoglobinopathies in that cast.